Survival benefit of primary prevention implantable cardioverter‐defibrillator/cardiac resynchronization therapy with a defibrillator: Analysis of the Japan cardiac device treatment registry and Japanese cardiac registry of heart failure in cardiology - Hisashi Yokoshiki; Masaya Watanabe; Sanae Hamaguchi; Hiroyuki Tsutsui; Akihiko Shimizu; Takeshi Mitsuhashi; Kohei Ishibashi; Tomoyuki Kabutoya; Yasuhiro Yoshiga; Yusuke Kondo; Taro Temma; Masahiko Takagi; et al. (Journal of Arrhythmia)
Abstract Background Evidence supporting the benefit from primary prevention implantable cardioverter‐defibrillator (ICD)/cardiac resynchronization therapy with a defibrillator (CRT‐D) for heart failure with reduced ejection fraction (HFrEF) is scarce in real‐world settings. Methods We analyzed propensity score matched cohorts of patients eligible for Sudden Cardiac Death in Heart Failure Trial (SCD‐HeFT) from Japan cardiac device treatment registry (JCDTR) and Japanese Cardiac Registry of Heart Failure in Cardiology (JCARE‐CARD). The former served as the defibrillator therapy group and the latter as the conventional therapy group. Results During an average follow‐up of 24 months, death occurred in 35 of 285 patients (12%) with defibrillator therapy and 65 of 285 patients (23%) with conventional therapy. Adjusted hazard ratios of all‐cause death, sudden death, heart failure death, and noncardiac death in defibrillator versus conventional therapy were 0.616 (95% confidence interval [CI]: 0.402–0.943, p = 0.026), 0.274 (95% CI: 0.103–0.731, p = 0.0097), 0.362 (95% CI: 0.172–0.764, p = 0.0077) and 1.45 (95% CI: 0.711–2.949, p = 0.31). After accounting for death without appropriate defibrillator therapy as a competing risk, the cumulative incidence of first appropriate defibrillator therapy in the defibrillator therapy group was nearly identical to that of all‐cause death in the conventional therapy group. Subgroup analyses indicated a lack of defibrillator benefit in patients with hypertension (p = 0.01 for interaction). Conclusions Primary prevention ICD/CRT‐D reduced the risk of all‐cause mortality of patients with HFrEF eligible for SCD‐HeFT compared to conventional therapy in the real‐world cohort.